Meaning and Grammar of Nouns and Verbs - Gerland, Doris; Ortmann, Albert; Latrouite, Anja; Horn, Christian (Studies in Language and Cognition, 2021)
The papers collected in this book cover contemporary and original research on semantic and grammatical issues of nouns and noun phrases, verbs and sentences, and aspects of the combination of nouns and verbs, in a great variety of languages. A special focus is put on noun types, tense and aspect semantics, granularity of verb meaning, and subcompositionality. The investigated languages and language groups include Austronesian, East Asian, Slavic, German, English, Hungarian and Lakhota. The collection provided in this book will be of interest to researchers and advanced students specialising in the fields of semantics, morphology, syntax, typology, and cognitive sciences.